2012
DOI: 10.1002/cbm.1825
|View full text |Cite
|
Sign up to set email alerts
|

Service user involvement in risk assessment and management: The Transition Inventory

Abstract: The TI provides a way to increase service user involvement in the assessments that determine when and how they transfer to settings where they will have more independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Involving and educating patients in the risk assessment and management process could potentially aid and improve such assessments (Skeem et al, 2013), improve patient satisfaction with care (Dixon, 2012;Livingston et al, 2013) and care outcome (Holliday et al, 2013). Patient involvement could also improve understanding of patient perspectives and encourage a sense of responsibility (Kroner, 2012), support resilience, confidence and self-management, promotes collaboration in their care plan and supports them in managing their own risk factors for violence (Gough, et al, 2015). Eidhammer et al (2014) point out that some information can only be provided by patients themselves.…”
Section: Patient Participation and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Involving and educating patients in the risk assessment and management process could potentially aid and improve such assessments (Skeem et al, 2013), improve patient satisfaction with care (Dixon, 2012;Livingston et al, 2013) and care outcome (Holliday et al, 2013). Patient involvement could also improve understanding of patient perspectives and encourage a sense of responsibility (Kroner, 2012), support resilience, confidence and self-management, promotes collaboration in their care plan and supports them in managing their own risk factors for violence (Gough, et al, 2015). Eidhammer et al (2014) point out that some information can only be provided by patients themselves.…”
Section: Patient Participation and Perspectivesmentioning
confidence: 99%
“…However, patients' perceptions in forensic and psychiatric in-settings have traditionally often not been included in research or in clinical risk assessments (Judges et al, 2016;Gough, et al, 2015;Langan, 2010;Dixon, 2012;Kroner, 2012;Sullivan, 2005;Olsson et al, 2015) or in risk management intervention programmes (Eidhammer et al, 2014). Some patients are not even aware that assessments of their future risk for violence are being conducted and communicated to other stakeholders (Gough, et al, 2015;Dixon, 2012;Langan, 2010).…”
Section: Patient Participation and Perspectivesmentioning
confidence: 99%
“…Similarly, if they were involved previously and there is no new risk information to record, there may have been a reluctance from staff to consult them again (even though they may have brought a unique risk perspective at that particular point in time). 5,6 Even if service users do not wish to be involved, it is worth considering the disappointment that carers have expressed at their lack of involvement in the risk assessment process. 7 If service users do not wish to be involved, then consent could be sought from them to involve their carer instead.…”
Section: Procedural Challengesmentioning
confidence: 99%
“…3 When service users have been interviewed about their involvement in risk assessment, most said that they were not told that risk assessments about them had been completed, or assumed that they had been without their involvement. 4 Because service users may have appropriate self-knowledge to predict their own future attitudes and actions, 5 involvement in risk assessment offers the benefit of self-prediction compared to prediction by others. 3,6 A recent national inquiry into suicide and safety within the UK indicated that service users and carers emphasised the importance of their involvement in risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…It may lead to a better understanding of the patient's perspective. It also increases the likelihood that patients take responsibility for their own actions and further development (Kroner ).…”
Section: Introductionmentioning
confidence: 99%